2021
DOI: 10.1371/journal.pntd.0008990
|View full text |Cite
|
Sign up to set email alerts
|

The temporospatial epidemiology of rheumatic heart disease in Far North Queensland, tropical Australia 1997–2017; impact of socioeconomic status on disease burden, severity and access to care

Abstract: Background The incidence of rheumatic heart disease (RHD) among Indigenous Australians remains one of the highest in the world. Many studies have highlighted the relationship between the social determinants of health and RHD, but few have used registry data to link socioeconomic disadvantage to the delivery of patient care and long-term outcomes. Methods A retrospective study of individuals living with RHD in Far North Queensland (FNQ), Australia between 1997 and 2017. Patients were identified using the Quee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
(22 reference statements)
0
27
0
Order By: Relevance
“…This current study's data lead to the greater truth that while almost all the patients in this cohort presented PLOS NEGLECTED TROPICAL DISEASES acutely, their clinical presentation and death from melioidosis was, in many cases, decades in the making. Despite Australia's universal health system, this finding is not unique to melioidosis; an association with socioeconomic disadvantage is seen in a variety of infectious diseases and non-communicable diseases seen in the region [13,[26][27][28][29][30][31][32].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This current study's data lead to the greater truth that while almost all the patients in this cohort presented PLOS NEGLECTED TROPICAL DISEASES acutely, their clinical presentation and death from melioidosis was, in many cases, decades in the making. Despite Australia's universal health system, this finding is not unique to melioidosis; an association with socioeconomic disadvantage is seen in a variety of infectious diseases and non-communicable diseases seen in the region [13,[26][27][28][29][30][31][32].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…However, the local incidence of melioidosis is rising and a more integrated approach to disease prevention and management is clearly necessary. Whilst a hub and spoke model has worked well in delivering specialist medical assessment and treatment in FNQ [29,39], providing interventions that prevent melioidosis in the geographically dispersed population is more complicated. Public health strategies that focus on human behaviour and aim to prevent exposure to B. pseudomallei are challenging to implement [40,41].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…21 The SEIFA score has been shown to have a strong inverse correlation with the prevalence of RHD in the region. 22 This study has many limitations. The small sample size increases the risk of type 2 statistical errors, and its retrospective design increases the likelihood of incomplete or inaccurate data.…”
mentioning
confidence: 94%
“…For example, a recent report by Kang and colleagues showed that the mean age of death of Australian Aboriginal patients with RHD was only 29 years. 5 However, there is a sparsity of literature published on rheumatic surgery in the New Zealand indigenous population, with limited reports particularly from the 21st century. 6 Furthermore, there is a paucity of global data on rheumatic surgery in young adults; most studies investigate outcomes in the paediatric population or older patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Without access to timely cardiac valvular surgery, patients with RHD have a significantly reduced lifespan. For example, a recent report by Kang and colleagues showed that the mean age of death of Australian Aboriginal patients with RHD was only 29 years 5 . However, there is a sparsity of literature published on rheumatic surgery in the New Zealand indigenous population, with limited reports particularly from the 21st century 6 .…”
Section: Introductionmentioning
confidence: 99%